STUDENTS’ PERCEPTIONS ON THE USE OF AI IN READING COURSES - Deah Amanda Putri; Ayu Antika; Loeis Alwina; Yupika Maryansyah (Teaching English and Language Learning English Journal, 2025)
This research investigates the viewpoints of 19 English Education students at Universitas Muhammadiyah Bengkulu regarding the utilization of AI tools, specifically ChatGPT, in EFL reading classes. Based on the Technology Acceptance Model (TAM), Social Constructivism, Cognitive Load Theory, and the Theory of Planned Behavior, a mixed-methods study demonstrated that students perceived AI as beneficial for enhancing their vocabulary, comprehension, and motivation. Although AI enhanced engagement and effectiveness, worries centered around reliance, inaccuracies, and diminished critical reading skills. Qualitative data supported these findings, highlighting students' desires for more explicit direction on the ethical and effective use of AI. The results highlight the importance of a harmonious integration of AI, stressing the necessity of digital literacy, responsible usage, and human supervision in reading education.